Inheritance of kernel quality attributes in quality protein maize (Zea mays L.) - Agrawal, V.K.; Singh, R.M.; Shahi, J.P.; Agrawal, R.K.; Chaudhary, D.P. (The Indian Journal of Genetics and Plant Breeding, 2016)
Nature and magnitude of gene actions were studied employing Hayman’s component analysis, with 8 quality protein maize (QPM) inbred lines and their 56 diallel set of crosses including reciprocals. Kernels of each entry were subjected to analysis of endosperm modification (EM), endosperm protein content (EPR) and tryptophan content (TRP). Significant difference was observed among genotypes for the three traits. EM and TRP content exhibited importance of both additive and dominance components, whereas EPR exhibited prevalence of dominance gene effects. Average degree of dominance revealed partial to complete dominance for EM, whereas complete to overdominance was exhibited by TRP, over the seasons. EPR consistently showed over-dominance. The quality traits among QPM lines were observed to be controlled by 1-3 dominant genes/gene blocks. Heritability estimates ranged from 55-75.5% for EM, 32.2-51% for EPR and 35.3-60.6% for TRP over three seasons.